INFLUENCE OF FLY ASH AND SLAGS OF BOILER WITH CIRCULATING FLUIDIZED BED ON PROPERTIES OF CONCRETE - Bondar, V.; Akhmednabiyev, Р. М.; Akhmednabiyev, R. R. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The properties of fly ash and slag of boilers with circulating fluidized bed are under consideration. In the Donetsk region several new generations of boilers are operating, permitting to burn the poor fossil fuels, including coal tailings. The ash and slag produced in this case are having somewhat different properties in contrast to the conventional waste TPP. In the study of fly ash and slag’s properties, the up-to-date methods are applied, based on X-ray phase (XRD), DT and spectral analyses. The question of the allocation of a large area of land for the storage of waste at thermal power plants. It was found that in windy weather wastes soar into the air, creating a cloud of dust and chemicals dissolved in rainwater and contaminate groundwater The aim of the present study is to identify the influence of fly ash on the strength properties of heavy concrete and on its resistance to water saturation and drying. The research strength of concrete based on mathematical experiment planning Keywords: Fly ash, ash and slag, boilers with a circulating fluidized bed, strength, concrete.